The Association Between Neonatal Polycythemia, Hypocalcemia, and Hypoglycemia - Abdurachman Sukadi; S. Fatimah Endropranoto; Wibisono Suwarno; Hadiawati Sastranegara (Indonesian Pediatric Society, 1989)
A study about the association between neonatal polycythemia, hypoglycemia, and hypocalcemia was carried out at the Hasan Sadikin General Hospital Bandung, Indonesia, between November 1986 and August 1987. Fourty-six neonates with polycythemia were enrolled in the study and 92 neonates born during the same period formed the control subjects. The control subject neonates were sampled among those with equal birth weight and gestational age compared to the polycythemia subjects. Blood glucose levels were examined more than three hours after birth and before the first feeding by using the God-PAP method and blood calcium levels at less than 24 hours of age by using calorimetric method. The cut-off point for hypoglycemia and hypocalcemia were 30 mg% and 7 mg%, respectively. The results showed that there was a significant difference for hypoglycemia (p < 0,01) and hypocalcemia (p < 0.05) between the exposed subjects and the control subjects